Organizational Workforce Transformation: E-Government as a Bridge with Digital Capabilities and Monitoring Medias - Yasar, M. Athok Ibnu; Soelistya, Djoko; Desembrianita, Eva (MANAZHIM, 2024)
The concept of good government (good government governance) is one of the elements that must be intertwined with thE-Government and the private sector. The aim of this research is to determine the influence of E-Government and Employee Commitment on improving employee performance through Digital Competence at the Greater Surabaya General Election Supervisory Agency. This study uses a quantitative approach. The data collection technique used in this research is Google Form. Data analysis was carried out through direct and indirect influence tests. This test was carried out using the SmartPLS statistical program and looked at the total direct effect and indirect effect calculations. The results of this research are that employee commitment has a positive and significant direct influence on employee performance, employee commitment has a positive and significant direct influence on digital competence, digital competency has a positive and significant direct influence on employee performance, E-Government has an influence positive and significant direct influence on employee performance, while the indirect influence is that employee commitment has a positive and significant direct influence on employee performance through digital competency as mediation, and digital competency functions as partial mediation, and for E-Government it has a positive direct influence and significant to employee performance through digital competence as mediation, where competence functions as partial mediation. This means that the better the implementation of E-Government and Employee Commitment, the greater the increase in Digital Competence so that it can improve employee performance at the Greater Surabaya General Election Supervisory Agency.